Kidney Transplant Outcome Is Associated with Regulatory T Cell Population and Gene Expression Early after Transplantation - Magdalena Krajewska; Katarzyna Kościelska-Kasprzak; Dorota Kamińska; Marcelina Żabińska; Marta Myszka-Kozłowska; Agnieszka Gomułkiewicz; Piotr Dzięgiel; Marian Klinger (Journal of Immunology Research)
Successful long-term kidney allograft survival with parallel reduction of complications resulting from prolonged immunosuppressive treatment is a goal in kidney transplantation. We studied the immune changes in cell phenotypes and gene expression induced by kidney transplantation. Our goal was to find a phenotypic and/or transcriptional pattern that might be considered prognostic for the kidney transplant outcome. The analysis was performed prospectively on 36 KTx recipients sampled during the first year and followed for five years after transplantation and on 40 long-term KTx recipients (7.9±2.2 y. post-KTx). The research involved flow cytometry assessment of lymphocyte subpopulations (including Tregs and CD3+CD8+CD28− lymphocytes) and gene expression analysis of immune-related genes (CD4, CD8, CTLA4, GZMB, FOXP3, IL10, IL4, ILR2A, NOTCH, PDCD1, PRF1, TGFB, and TNFA). The analysis of patterns observed over the first post-KTx year was confronted with control, pretransplant, and long-term transplant results. Treg counts at months one and three post-KTx correlated positively with the current and future allograft function. FOXP3 gene expression at month one post-KTx was also associated with long-term allograft function. The KTx-induced CD3+CD8+CD28− population correlated with GZMB and PRF1 expression and suggested their cytotoxic properties. The size of the Treg population and regulatory FOXP3 gene expression in the early period after transplantation are associated with kidney transplant outcome. The outlined predictive power of the Treg population needs to be investigated further to be confirmed as one of the immune monitoring strategies that may help achieve the best long-term kidney allograft outcomes.